Filamentous chaperone protein-based hydrogel stabilizes enzymes against thermal inactivation. Issue 45 (14th May 2021) - Xu, Dawei; Lim, Samuel; Cao, Yuhong; Abad, Abner; Kang, Aubrey Nayeon; Clark, Douglas S.
Abstract : We report a filamentous chaperone-based protein hydrogel capable of stabilizing enzymes against thermal inactivation. Abstract : We report a filamentous chaperone-based protein hydrogel capable of stabilizing enzymes against thermal inactivation. The hydrogel backbone consists of a thermostable chaperone protein, the gamma-prefoldin (γPFD) from Methanocaldococcus jannaschii, which self-assembles into a fibrous structure. Specific coiled-coil interactions engineered into the wildtype γPFD trigger the formation of a cross-linked network of protein filaments. The structure of the filamentous chaperone is preserved through the designed coiled-coil interactions. The resulting hydrogel enables entrapped enzymes to retain greater activity after exposure to high temperatures, presumably by virtue of the inherent chaperone activity of the γPFD.